Urgensi Pembentukan Undang-Undang Digital Banking Bagi Perbankan Syariah Di Indonesia - Muhammad Urfi Amrillah (Universitas Islam Indonesia, 2020)
This study aims to determine the legal regulation of digital banking in Indonesia and the urgency of digital banking regulation for Islamic banking in Indonesia. This is a normative juridical research that uses a statutory approach. The results conclude that digital banking provisions are regulated in OJK Regulation No.12/POJK.03/2018 on the Implementation of Digital Banking Services by Commercial Banks in lieu of Law Number 7 of 1992 jo. Law Number 10 of 1998 on Banking does not regulate digital banking provisions. The urgency of digital banking regulations for Islamic banking in Indonesia can be viewed from several aspects, namely: first, the philosophical aspect, which are the special regulations related to digital banking for Islamic banking in Indonesia, that is mandated in Article 33 paragraphs (1) and (4) of the 1945 Constitution. Second, the sociological aspect, which is the case of a digital account burglary experienced by one of the customers as a result of the absence of strong regulations such as laws governing digital banking, especially for Islamic banking in Indonesia. Third, the juridical aspect, which is that digital banking is legally regulated in the OJK Regulation so that it has not been able to overcome the problems that occur, especially in the implementation of digital banking for Islamic banking, given the weakness of the binding power of the regulation